Zbtb20 modulates the sequential generation of neuronal layers in developing cortex. Issue 1 (December 2016) - Tonchev, Anton; Tuoc, Tran; Rosenthal, Eva; Studer, Michèle; Stoykova, Anastassia
Abstract Background During corticogenesis, genetic programs encoded in progenitor cells at different developmental stages and inherited in postmitotic neurons specify distinct layer and area identities. Transcription factor Zbtb20 has been shown to play a role for hippocampal development but whether it is implicated in mammalian neocortical morphogenesis remains unknown. Results Here, we report that during embyogenesis transcription factorZbtb20 has a dynamic spatio-temporal expression pattern in mitotic cortical progenitors through which it modulates the sequential generation of cortical neuronal layer identities.Zbtb20 knock out mice exhibited enhanced populations of early born L6-L4 neuronal subtypes and a dramatic reduction of the late born L3/L2 neurons. This defect was due to a temporal misbalance in the production of earlier versus later born neurons, leading to a progressive diminishing of the progenitor pool for the generation of L3-L2 neurons. Zbtb20 implements these temporal effects in part by binding to promoter of the orphan nuclear receptorCoupTF1/Nr2f1. In addition to its effects exerted in cortical progenitors, the postmitotic expression of Zbtb20 in L3/L2 neurons starting at birth may contribute to their proper differentiation and migration. Conclusions Our findings revealZbtb20 as a novel temporal regulator for the generation of layer-specific neuronal identities.